PENGAWASAN TERHADAP WARGA NEGARA ASING OLEH KANTOR IMIGRASI KELAS 1 SURAKARTA DALAM ASEAN ECONOMIC COMMUNITY - GPH. Dipokusumo, Mas Ageng Banyubiru, Christy Damayanti & (Transformasi, 2016)
The context of the ASEAN Economic Community led to the freedom of movement ofprofessionals, business people, and workers in the ASEAN region, and with that aspects of theseinterests has been the holding of the Meeting of the ASEAN Directors-General of ImmigrationDepartment and Heads of Consular Affairs Divicions of the Ministries of Foreighn Affairsregarding ASEAN Framework Agreement on visa Exemtion . The meeting was a transboundaryfacilities for workers, businesses, and professionals to undertake activities in ASEAN Countries.The facility used to be foreign citizens tour, learn, and visiting family. Based on theory nationalsecurity, cooperated, transnatinal crime The author examines this research about foreign citizenoversight conducted by the Office of Immigration first Class of Surakarta on ASEAN EconomicCommunity. The author examines this research with qualitative research methods. The dataused are primary and secondary data with the use of primary subjects such as foreign citizenoversight conducted by the Office of Immigration first Class of Surakarta. ASEAN EconomicCommunity highlighted by the Immigration Office first class Surakarta since become a potentialthreat to foreign citizens who come to Indonesia, especially Surakarta with the emergence ofmany exchanges criminals who assist them in providing travel documents are counterfeit,sponsor false to obtain a entrance visa. This research resulted in 1. The potential of thesethreats solved by the Immigration Office first class Surakarta by: a. prevention with overseeingforeign citizens Movement. b. repression action to foreign citizens through legal channels 2.Immigration Office first class Surakarta create a special unit to oversee foreign citizen namedTim Pora. 3. Immigration Office First Class Surakarta significant role in the form of cooperation,national and regional security. Advice from the author is expected to discuss theimmigration movement of Indonesia.Key words : Surakarta‟s Imigration Office, Oversight, And Transnational Crime